2017
DOI: 10.1080/10408444.2017.1342599
|View full text |Cite|
|
Sign up to set email alerts
|

Persistence of mercury-induced motor and sensory neurotoxicity: systematic review of workers previously exposed to mercury vapor

Abstract: Background Elemental mercury (Hg0) is a well-recognized neurotoxicant, but it is uncertain whether and for how long its neurotoxicity persists. Among studies that evaluated previously-exposed workers, only one examined workers during and also years after exposure had ceased. Objective To create a series of ‘synthetic’ longitudinal studies to address the question of persistence of Hg0 neurotoxicity in occupationally exposed workers. Methods We systematically reviewed studies describing objective motor and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
6
0
3
Order By: Relevance
“…The study did not support a link between mercury and ET. Action tremor has been a well-described outcome of mercury exposure in a broad and varied range of settings in numerous studies spanning many years [18][19][20], and further interest in mercury relates to the fact that it is toxic to the Purkinje cell population in the cerebellum [54,55], a population of neurons increasingly linked to the pathophysiology of ET [56][57][58]. With respect to ET, specifically, however, we are unaware of any study that has directly compared mercury exposures in ET cases versus controls or that has quantified and compared blood mercury concentrations in ET cases versus controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study did not support a link between mercury and ET. Action tremor has been a well-described outcome of mercury exposure in a broad and varied range of settings in numerous studies spanning many years [18][19][20], and further interest in mercury relates to the fact that it is toxic to the Purkinje cell population in the cerebellum [54,55], a population of neurons increasingly linked to the pathophysiology of ET [56][57][58]. With respect to ET, specifically, however, we are unaware of any study that has directly compared mercury exposures in ET cases versus controls or that has quantified and compared blood mercury concentrations in ET cases versus controls.…”
Section: Discussionmentioning
confidence: 99%
“…Other neurotoxins are tremor producing. Mercury is one of these, and it has long been linked with tremor [18][19][20]. Yet curiously, we are unaware of any studies directly assessing the links between mercury and ET.…”
Section: Introductionmentioning
confidence: 99%
“…These data have a number of clear utilities. First, in both occupational medicine and toxicologic-epidemiology, which often focus on the development of abnormal neurological outcomes such as hand tremor [15][16][17][18], it is imperative to establish normal levels of tremor within age-and gender-defined strata. In genetic studies of ET and other tremor disorders, it is imperative to establish background levels of normal tremor; these are often influenced by advancing and advanced age [19].…”
Section: Discussionmentioning
confidence: 99%
“…For example, such tremor may impair precise hand control in professional musicians [4,5], and is a source of impaired motor performance in professional sports [6], among surgeons [7][8][9], in airplane pilots [10], and it can impede effective shooting performance in military personnel [11][12][13][14]. In occupational medicine and toxicologicepidemiology, which often focus on the development of abnormal neurological outcomes (e.g., hand tremor) [15][16][17][18], it is important to establish normal levels of tremor within ageand gender-defined strata. In genetic studies of essential tremor (ET), background levels of normal tremor are important to gauge in order to assign valid diagnoses to at-risk family members across the full range of age and gender strata [19].…”
Section: Introductionmentioning
confidence: 99%
“…Mercury (Hg) is a naturally occurring heavy metal of great concern to public health. Ample research has demonstrated that exposure to various forms of Hg is associated with impaired neurodevelopment [1][2][3], nervous system effects in adults [4][5][6], cardiovascular diseases [7,8], and renal toxicity [9,10]. Globally, the World Health Organization (WHO) has designated Hg as one of the ten most dangerous chemicals to public health [11].…”
Section: Introductionmentioning
confidence: 99%